Potensi pengembangan produk baru onde-onde edamame [Potency of edamame onde-onde new product development] - Ida Bagus Suryaningrat; Nidya Shara Mahardika; Latifatul Karimah (Jurnal Teknologi & Industri Hasil Pertanian, 2022)
Edamame onde-onde is a new traditional food product processed using edamame soybeans. As a new product, it is necessary to know the best formulation of onde-onde edamame that potential consumers prefer. In addition, edamame onde-onde may have a risk of failure in the process of launching in the market. This study aimed to determine the formulation of edamame onde-onde products according to predetermined criteria, analyze perceptions of edamame onde-onde products, and plan marketing concepts related to segmentation, targeting, and positioning.  Perceptions and marketing plan data were analyzed using cross-tabulation, clusters, and multidimensional scaling tests. The best formulation for making edamame onde-onde was the 30% formulation, which used edamame beans to glutinous rice flour ratio of 3:1. The selected target market was female consumers aged 36-45 years, with a diploma degree, and private employees with Rp income. 5,000,000-Rp. 10,000,000 and expenses of Rp. 1,000,000-Rp. 5,000,000. Product position attributes that differentiated edamame onde-onde products were a delicious taste, easy to obtain, affordable prices, and highly nutritious.Keywords: edamame onde-onde, perception, plan marketing concept, product development